Evaluating lay perceptions of maternal mortality to improve risk communication: a case study in Rivers State, Nigeria. Issue 6 (3rd June 2017) - Oyibo, Natasha; Weller, Gordon; Watt, John
ABSTRACT: Maternal mortality is one of the major challenges in reproductive health in Nigeria. Approximately two-thirds of the women (three quarters in rural Nigeria) deliver their babies outside of health facilities and without medically skilled birth attendants. Communication and education are vital since so many births take place outside formal health care environments, and the high mortality rate suggests there is potential for progress, which can supplement Nigerian government efforts. The purpose of the study was to elicit lay knowledge and interpretations about the major components of the problem as part of a wider mental models study aimed at improving risk communication. These knowledge and perceptions were elicited through semi-structured interviews with women of childbearing age (15–49 years). Interviews were analysed to evaluate common themes that will be used to model lay perceptions for comparison to the expert mental model as part of the wider method. The emergent themes will be presented and discussed in the context of the identification of important gaps in knowledge and misperceptions that have the potential for development of improved risk communication.